IMPLEMENTASI MEDIA “BUSUPRI: BELAJAR UNSUR SURAT PRIBADI” DENGAN MODEL CIRC (COOPERATIVE INTEGRATED READING AND COMPOSITION) MENINGKATKAN KETERAMPILAN MENULIS SISWA KELAS V SD NEGERI SAMPANGAN 02 KOTA SEMARANG - Dellayla Ayu Az Zahra; Ida Zulaeha; Panca Dewi Purwati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research focuses on describing learning by implementing innovative learning media in Indonesian language with Cooperative Integrated Reading and Composition learning model in class V at SD Negeri Sampangan 02 Semarang City. This research method uses Mixed Method, which is a combination of qualitative and quantitative approaches. The problems identified in the study were the low writing skills of students, the lack of varied learning media, and the saturation of the use of learning models. Based on the results of the study, there was a significant increase in the t-test of 0.0000154 and the n-gain test of 65.68% with a fairly effective category. It can be concluded based on the tests carried out that Ha is accepted and Ho is rejected. So that the implementation of innovative Indonesian learning media ‘BUSUPRI: learning the elements of personal letters’ with the CIRC (Cooperative Integrated Reading and Composition) model is proven to improve the writing skills of fifth grade students of SD Negeri Sampangan 02 Semarang City.